Juridical Implications for Notaries who are appointed as House of Representatives in the Conception of Legal Certainty - Nabila, Poppy Sarah Hasna (Jurnal Konstatering, 2023)
All elements of society certainly have the same obligations and rights, in the eyes of state law. In essence, those who will represent certain elements of society must be bound by the provisions of the laws in force in Indonesia. The People in the Conception of Legal Certaintyâ€. The research method used is a qualitative approach, namely a way or research method that emphasizes analysis or descriptive. In a qualitative research process things that are subject perspectives are emphasized more and theoretical foundations are used by researchers as guides, so that the research process is in accordance with the facts encountered in the field when conducting research, in the form of interviews with Notaries to find relationships (correlations) between various symptoms or variables as a data collection tool consisting of document studies, observations (observations), and interviews (interviews). Based on the research results, there are the results of the judge's legal considerations in determining civil cases concerning Juridical Implications for Notaries who are appointed to the People's Legislative Assembly in the Conception of Legal Certainty. become a member of the People's Legislative Assembly, based on Article 17 letter d UUJN regarding the prohibition of concurrent positions as state officials. Then the notary is obliged to apply for leave, and appoint a substitute notary (Article 11 paragraph (1-3) UUJN). Which reads: (1) Notaries who are appointed as state officials are required to take leave. (2) Leave as referred to in paragraph (1) applies as long as the Notary holds office as a state official. (3) Further provisions regarding Notary leave as referred to in paragraph ( 1) regulated by Ministerial Regulation. and the Responsibilities of a Notary Who Is Appointed to be a Member of the People's Legislative Assembly for Deeds That Have Been Issued When They Cause a Loss of Other Parties, namely the Notary who makes the deed is responsible for the deed he made, even though the notary who made the deed is on leave while he is a member of the People's Representative Council and has appointed a notary substitute as recipient of the notary protocol. The legal basis is Article 65 UUJN. Keywords: Certainty; Notary; Representatives.